Pengembangan Komunitas Kristen Menangani Fear of Missing out (FOMO) di Era Digital - Poerwanto, Charles; Hermanto, Yanto Paulus (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
The phenomenon of FOMO (Fear of Missing Out) in the digital era has become a serious challenge impacting the mental health of church members, leading to anxiety, stress, and even depression if not properly addressed. This study aims to understand the impact of FOMO and explore the strategies and programs of churches in supporting the mental health and spiritual well-being of their congregants. This research uses a qualitative approach with literature review and a brief survey method. It identifies various efforts that churches can take to address FOMO. The results indicate that churches can mitigate the effects of FOMO by building a social support system that fosters closeness among church members, including spiritual retreats, workshops, counseling services, and mentoring programs. These findings provide practical guidance for churches to strengthen the Christian community as a safe and supportive place for individuals struggling with FOMO. To implement this, churches can form specialized support groups, integrate education about FOMO into sermons and discipleship classes, and wisely use digital media to create a more interactive and supportive community. Thus, the church plays an active role in creating a more inclusive, loving environment that promotes the holistic well-being of its members amid the challenges of the digital era.